2021
DOI: 10.1002/cey2.145
|View full text |Cite
|
Sign up to set email alerts
|

Regulating adsorption ability toward polysulfides in a porous carbon/Cu3P hybrid for an ultrastable high‐temperature lithium–sulfur battery

Abstract: Lithium-sulfur batteries (LSBs) can work at high temperatures, but they suffer from poor cycle life stability due to the "shuttle effect" of polysulfides. In this study, pollen-derived porous carbon/cuprous phosphide (PC/Cu 3 P) hybrids were rationally synthesized using a one-step carbonization method using pollen as the source material, acting as the sulfur host for LSBs. In the hybrid, polar Cu 3 P can markedly inhibit the "shuttle effect" by regulating the adsorption ability toward polysulfides, as confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…[ 27–33 ] Previous research identified that doped heteroatoms (B, N, and P) on carbon hosts could restrict the shuttle effect of polyselenides in Li/Na‐Se batteries with organic electrolytes. [ 34,35 ] However, the effect and mechanism of heteroatom‐doped carbon confining polyselenides were far from full recognition in Zn–Se batteries. Thus, exploring the effect and mechanism of doping heteroatoms (B, N, and P) on carbon hosts in polyselenide adsorption is of paramount importance for Zn–Se batteries with enhanced, long‐lasting performance.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27–33 ] Previous research identified that doped heteroatoms (B, N, and P) on carbon hosts could restrict the shuttle effect of polyselenides in Li/Na‐Se batteries with organic electrolytes. [ 34,35 ] However, the effect and mechanism of heteroatom‐doped carbon confining polyselenides were far from full recognition in Zn–Se batteries. Thus, exploring the effect and mechanism of doping heteroatoms (B, N, and P) on carbon hosts in polyselenide adsorption is of paramount importance for Zn–Se batteries with enhanced, long‐lasting performance.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the practical application of water electrolysis is severely restricted by the OER process, and highly efficient catalyst materials are desired. [10][11][12] Limited by the high cost and rareness of noble metals, attention has been focused on 3d-transition metal-based non-noble materials like phosphides, [13][14][15] sulfides, 16,17 and selenides. 18 While these catalysts have a delayed reaction in the active phase of high-valence-state metal species formation, increasing the polarity would be useful to overcome the thermodynamic uphill process of O-H bond cleavage and O-O bond formation.…”
mentioning
confidence: 99%
“…Recently, a large amount of efforts have been made to synthesize new separator modifying materials, such as heteroatom-doped carbon materials, , metal carbides, metal oxides, spinels, and perovskites, which can interact strongly with polysulfides. Transition-metal phosphides, such as Ni 2 P, FeP, Cu 3 P, and NiCoP, have attracted academic attention due to their good electrochemical stability, low charge–discharge polarization voltage, and strong polarity. It has been reported that Ni 2 P is a very promising material due to low decomposition energy barriers of Li 2 S and strong interactions with polysulfides .…”
Section: Introductionmentioning
confidence: 99%